2010
DOI: 10.1086/655899
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Autochthonous Hepatitis E Virus Infection in Solid‐Organ Transplant Recipients in France

Abstract: Immunocompromised patients should avoid eating insufficiently cooked game meat or pork products so as to reduce the risk of HEV infection and chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 48 publications
(72 reference statements)
3
141
1
3
Order By: Relevance
“…A case-control study among transplant recipients in MP found a significant association between HEV infection and the consumption of game meat [20]. The virus was detected in the livers of wild boar from the forests of the Ariège and Aude; these virus strains were very similar, genomically, to those isolated from patients suffering from hepatitis E (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…A case-control study among transplant recipients in MP found a significant association between HEV infection and the consumption of game meat [20]. The virus was detected in the livers of wild boar from the forests of the Ariège and Aude; these virus strains were very similar, genomically, to those isolated from patients suffering from hepatitis E (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Also levels of IgM, IgG anti-HEV antibodies and HEV RNA during acute infection phase were not predictive of whether or not the infection will become chronic. In acute phase itself, only 24% had abnormal bilirubin levels [25] . This further emphasizes that an acute HEV infection can be easily missed unless clinician had a high index of suspicion.…”
Section: High Index Of Suspicionmentioning
confidence: 96%
“…However, 4 y ago a case of chronic hepatitis E was identified in Europe, and since then chronicity has been documented in immunocompromised solid-organ transplant recipients and HIVinfected individuals (4)(5)(6)(7). Although hepatitis E infection generally causes mild to moderate disease, it occasionally has caused fulminant liver failure in acute cases, in chronically infected patients, and especially in those with underlying chronic liver disease or pregnancy (1,2,(4)(5)(6)(7)(8). Additionally, hepatitis E has been misdiagnosed as drug-induced liver injury, thus complicating drug trials or treatment regimens (9).…”
mentioning
confidence: 99%